Short-term cold exposure supports human Treg induction in vivo - Becker, Maike; Serr, Isabelle; Salb, Victoria K.; Ott, Verena B.; Mengel, Laura; Blüher, Matthias; Weigmann, Benno; Hauner, Hans; Tschöp, Matthias H.; Daniel, Carolin (Molecular Metabolism, 2019)
Obesity and type-2 diabetes (T2D) are metabolic diseases that represent a critical health problem worldwide. Metabolic disease is differentially associated with fat distribution, while visceral white adipose tissue (VAT) is particularly prone to obesity-associated inflammation. Next to their canonical function of immune suppression, regulatory T cells (Tregs) are key in controlling adipose tissue homeostasis. Towards understanding the molecular underpinnings of metabolic disease, we focus on how environmental-metabolic stimuli impinge on the functional interplay between Tregs and adipose tissue. Here, cold exposure or beta3-adrenergic signaling are a promising tool to increase energy expenditure by activating brown adipose tissue, as well as by reducing local inflammation within fat depots by supporting immunosuppressive Tregs. However, in humans, the underlying mechanisms that enable the environmental-immune crosstalk in the periphery and in the respective tissue remain currently unknown. We used combinatorial approaches of next generation humanized mouse models and in vitro and in vivo experiments together with beta3-adrenergic stimulation to dissect the underlying mechanisms of human Treg induction exposed to environmental stimuli such as cold. To test the translational relevance of our findings, we analyzed samples from the FREECE study in which human subjects were exposed to individualized cooling protocols. Samples were analyzed ex vivo and after in vitro Treg induction using qRT-PCR, immunofluorescence, as well as with multicolor flow cytometry and cell sorting. In vivo application of the beta3-adrenergic receptor agonist mirabegron in humanized mice induced thermogenesis and improved the Treg induction capacity of naïve T cells isolated from these animals. Using samples from the human FREECE study, we demonstrate that a short-term cold stimulus supports human Treg induction in vitro and in vivo. Mechanistically, we identify BORCS6 encoding the Ragulator-interacting protein C17orf59 to be significantly induced in human CD4+ T cells upon short-term cold exposure. Strong mTOR signaling is known to limit successful Treg induction and thus likely by interfering with mTOR activation at lysosomal surfaces, C17orf59 improves the Treg induction capacity of human naïve T cells upon cold exposure. These novel insights into the molecular underpinnings of human Treg induction suggest an important role of Tregs in linking environmental stimuli with adipose tissue function and metabolic diseases. Moreover, these discoveries shed new light on potential approaches towards tailored anti-inflammatory concepts that support human adipose tissue homeostasis by enabling Tregs. •Beta3-adrenergic stimulation enhances human Tregs in humanized mice.•Short-term cold stimulation increases human Treg induction in vitro and in vivo.•Short-term cold exposure elevates human Treg signatures genes.•Short-term cold induces BORCS6 encoding C17orf59 in human CD4+T cells.•C17orf59 limits mTOR signaling and thereby supports human Treg induction.